Efeitos Clínicos, Hemogasométricos e Ecocardiográficos da Associação da Dexmedetomidina e Metadona com ou sem Midazolam em Felinos - Bruna Maia Cerqueira Câmara (2020)
The population of cats in households is booming, and may, in some years, exceed the population of dogs. Because it's lower tolerance to manipulation and greater stress under containment, it is necessary to research and evaluate the effects of different sedation / chemical restraint protocols. The sedative, cardiorespiratory, echocardiographic and hemogasometric effects of dexmedetomidine and methadone associated or not with midazolam were compared. Eighteen healthy young cats (4.06 ± 0.48 kg) were randomly sedated with two protocols, through the intramuscular route: dexmedetomidine (5ug/kg), methadone (0,3 mg/kg) and midazolam (0,3 mg/kg) (DMTM, n=9) or dexmedetomidine (7,5ug/kg) and methadone (0,3mg/ kg) (DMT, n=9). The following cardiorespiratory parameters were evaluated: heart and respiratory rates, systolic, mean and diastolic invasive arterial blood pressures, pulse oximetry, rectal temperature, measured at baseline, 5 and 10 minutes after pharmacological latency. The sedation, analgesia and muscle relaxation scores were assessed before and 5 minutes after pharmacological latency, while arterial blood gas analysis and echocardiography echocardiography were assessed before and after 10 or 15 minutes, respectively. For data analysis, a split-plot design was used with the Tukey-adjusted test or the Wilcoxon test (p <0.05). There was no difference between the protocols regarding the cardiorespiratory, hemogasometric, and echocardiographic parameters used. The scores for sedation, analgesia and muscle relaxation also did not differ between the protocols, with the degree of sedation, analgesia and myorelaxation considered satisfactory in both groups. A significant decrease in HR was observed after administration of the sedative protocols, reaching a maximum reduction at T10 (46% and 53% reduction in the DMT and DMTM groups, respectively). The reduction in heart rate had an impact on echocardiographic parameters such as CO, which decreased 53% and 56% in the DMT and DMTM groups, respectively. There was a significant reduction in PaO2, SaO2, F. Ej and F. enc in both protocols. SpO2 decreased significantly after 5 minutes of sedation in the DMT group, but with a minimum mean SpO2 of 92% in T5. The respiratory rate decreased significantly at 5 and 10 minutes in the DMTM group, while PaCO2 increased in both groups, indicating respiratory depression caused by the drugs. We conclude both sedative protocols can be recommended for clinical sedation of young and healthy cats in the doses used. However, both protocols resulted in cardiorespiratory depression in cats and also the particularities of the animals should be evaluated regarding reducing cardiac output by more 50%.